Phylogeny of Helicoidei (Gastropoda: Stylommatophora) with special emphasis on the Chinese Camaenidae - Zhang, Guoyi (2023)
The Helicoidei Rafinesque, 1815 are a widely distributed and highly diverse infraorder of land snails and slugs. Here we constructed a phylogenetic tree based on sequences of the large subunit ribosomal RNA gene to investigate the relationships within the Helicoidei. Based on our phylogenetic tree, the Polygridae and the Camaenidae cluster together, the Hygromiidae is polyphyletic and the Solaropsidae are the sister group to a clade comprising other Sagdoidea. The results suggest that the Camaenidae and Polygyridae is composed of several lineages that the relationships between these are not resolved. Our findings also suggest that the Hygromiidae s. lat. families should be restored to their previous name, Hygromiidae, as in the taxonomy of Bouchet et al. (2005).